Changes in People's Habits From Conventional Shopping to Shopee E-commerce In Padangpanjang City, West Sumatra Province - Twidi Ramadhani; Yulika, Febri; Oktayanty, Yetty (Kirana Publisher (KNPub), 2024)
This research is entitled Changes in Community Habits from Conventional Shopping to Shopee E-commerce in Padangpanjang City, West Sumatra Province. The purpose of this study is to explain the factors that cause changes in shopping activities and how the form of change that occurs due to shopee E-commerce shopping habits. The theory used in this research is the modernization theory of Talcott Parsons. Talcott Parsons defines that the development process carried out by developing countries today can be achieved when following the process carried out by developed countries, distinguishing between